2014
DOI: 10.1080/19443994.2014.922290
|View full text |Cite
|
Sign up to set email alerts
|

Wet weather discharge characteristics of phosphorus and management implications in a mixed land-use watershed

Abstract: 2014): Wet weather discharge characteristics of phosphorus and management implications in a mixed land-use watershed, Desalination and Water Treatment, A B S T R A C TThe diffuse phosphorus (P) load to receiving waters has been of great concern because it is considered the main cause of eutrophication and algal bloom in natural waters. For establishing effective P control strategy, it is the important first step to obtain information on characteristics of diffuse source of P and its discharge behavior during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…These are discussed in more detail in Section 3.3.1. In addition, three studies reported stormwater runoff (Alfonso et al., 2015; Kumar et al., 2016) and soil solution (Zhang et al., 2019), the latter two studies using process‐based modeling. Kumar et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are discussed in more detail in Section 3.3.1. In addition, three studies reported stormwater runoff (Alfonso et al., 2015; Kumar et al., 2016) and soil solution (Zhang et al., 2019), the latter two studies using process‐based modeling. Kumar et al.…”
Section: Resultsmentioning
confidence: 99%
“…The data on which this article is based are available in Alfonso et al. (2015), Allison et al. (1998), Barr et al.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation